Barriers to entry and the role of African multinational corporations: Entrants in intermediate industrial products (inputs into construction) - Grace Nsomba; Thando Vilakazi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Effective competition in the Southern and East African regions requires independent rivals competing across borders and within domestic markets through innovation and effort, investment, product quality, and prices. To understand the constraints to more dynamic rivalry between firms within the region, this paper considers the obstacles to integration from the perspective of fostering the development of domestic firms with strong capabilities. Two emerging African multinational corporations involved in the manufacturing of intermediate industrial products that are inputs into the construction industry are studied in order to provide a new perspective on these issues. Drawing from interviews and publicly available information, this paper links existing literature on competition, barriers to entry, and inclusive regional growth to the experiences of the emerging identified African multinational corporations with the view to inform policy that encourages regional integration, the development of capabilities, technological investments, and, ultimately, growth and regional competition.
Keywords: L11; L14; L41; L52; 330; African multinational corporations; competition; regional integration; barriers to entry; dynamic rivalry